The effect of physical exercise and cognition-orientated interventions on post-stroke cognitive function: Protocol for an overview of reviews - James Smith; Philip Nagy; David Tod; Carol Holland; Hannah Jarvis (PLoS ONE, 2025)
Background Strokes are becoming more common, and with improving survival rates, the prevalence of stroke survivors has increased. Almost half of chronic stroke survivors are cognitively impaired, and healthcare services are struggling to manage these patients, leaving some feeling “abandoned”. Several systematic reviews have investigated the effect of physical exercise and cognition-orientated interventions on post-stroke cognitive impairment, and have produced conflicting findings, making it difficult for clinicians and guideline producers to make evidence-based decisions. This overview of reviews aims to provide a comprehensive overview of systematic reviews investigating the effect of physical exercise and cognition-orientated interventions on post-stroke cognitive function, assess methodological quality and certainty of evidence, and identify sources of discordance between these reviews. Methods Eight databases–Embase, Medline, CINAHL, Psycinfo, SPORTDiscus, The Cochrane Database of Systematic reviews, Epistemonikos, and Scopus–plus grey literature sources will be searched. The eligibility criteria include systematic reviews of trials that included an adult stroke population and investigated physical exercise and/or cognition-orientated interventions. Only reviews that assessed at least one of the DSM-5 neurocognitive domains will be included. Screening, data extraction, and quality appraisal will be conducted by two independent reviewers. Methodological quality, certainty of evidence, and primary study overlap will be assessed using the AMSTAR-2, GRADE, and GROOVE tools, respectively. Interventions will be grouped into exercise, cognition-orientated, and combined interventions, and findings will be synthesised narratively. Heterogeneity assessment will be conducted to identify factors causing discordance between reviews. Discussion The findings of this overview will allow decision makers to make evidence-based decisions, stratified by methodological quality and certainty of evidence. Heterogeneity assessment may identify factors causing discordance between systematic reviews, which could inform the design of future studies. Trial registration Registration: PROSPERO CRD42024534179.